In-situ polymerized 2D confined nanocomposite for visual enantioselective recognition - Qing Xu; Yi-Han Wen; Long Yi Jin; Hui-Yu Zhao; Yi-Rong Pei (Applied Clay Science, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Rare and underexplored lobane- and prenyleudesmane-type diterpenes primarily from corals with additional plant sources—Biosynthesis and pharmacological perspectives - Lo-Yun Chen; Bo-Rong Peng; You-Ying Chen; Huong-Giang Le; Ngoc-Thac Pham; Yi-Ying Lin; Hung-Yi Chen; Pei-Jhen Hsieh; Mohamed El-Shazly; Kuei-Hung Lai (Phytochemistry, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

An innovative bioactive ingredient preparation method without column chromatography and gel filtration: High-purity 3S,3'S- astaxanthin from bioresources - Wei-Cheng Yuan; Tung-Ying Wu; Pei-Yi Chu; Fang-Rong Chang; Yang-Chang Wu (Phytochemistry Letters, 2025)

Assessing 3-D variability of ultrafine particle using a Geo-AI modelling approach: A case study in Zhunan-Miaoli, Taiwan - Chia-Wei Hsu; Yinq-Rong Chern; Jun-Jun Su; Pei-Yi Wong; Aji Kusumaning Asri; Candera Wijaya; Yu-Cheng Chen; Shih-Chun Candice Lung; Ta-Chih Hsiao; Tee-Ann Teo; Yi-Liang Shih; Chih-Da Wu (Environmental Pollution, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Effect-based high-throughput screening of environmental water samples: Focus on liver toxicity pathways and endocrine disruption - Olivia Lautan; Ssu-Ning Chen; Chin-Ching Lu; Yi-Hsuan Huang; Hsiu-Ling Chen; Pei-Shan Chih; Rong-Jane Chen (Journal of Hazardous Materials, 2025)

Combining soy protein isolate and sorbitol as cryoprotectants for portuguese oysters (Crassostrea angulata) and investigating the effect on ice crystal damage - Chao-Kai Chang; Yi-Feng Kao; Huey-Jine Chai; Pei-Rong Liang; Wei-Lun Zhu; Kai Shyu; Ratna Sari Listyaningrum; Chang-Wei Hsieh (Food Chemistry, 2025)

Synergistic properties of single-component hexagonal iron borate for superior and sustainable photo-Fenton catalysis - Po-Yi Wu; Jing-Cheng Hsu; Tsung-Yueh Lin; Yu-Lun Zhu; Yu-Rong Chang; Pei Yuin Keng (Journal of Environmental Chemical Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Neuroprotection of isookanin against MPTP-induced cell death of SH-SY5Y cells via BCL2/BAX and PI3K/AKT pathways - Rong Zhang; Lili Teng; Yi Zhong; Pei Ma; Lijia Xu; Peigen Xiao (Psychopharmacology, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Toxicity prediction: An application of alternative testing and computational toxicology in contaminated groundwater sites in Taiwan - Rachelle D. Arcega; Rong-Jane Chen; Pei-Shan Chih; Yi-Hsuan Huang; Wei-Hsiang Chang; Ting-Khai Kong; Ching-Chang Lee; Trias Mahmudiono; Chun-Chih Tsui; Wen-Che Hou; Hsin-Ta Hsueh; Hsiu-Ling Chen (Journal of Environmental Management, 2023)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Influence of leaf shape on the scaling of leaf surface area and length in bamboo plants - Pei-Jian Shi; Yi-Rong Li; Ülo Niinemets; Edward Olson; Julian Schrader (Trees, 2021)
Key message Using more than 10,000 bamboo leaves, we found that the scaling between leaf surface area and length follows a uniform power law relationship mainly relying on the degree of variation in leaf shape (reflected by the ratio of leaf width to length). Abstract A recent study based on leaf data of different plant taxa showed that the scaling of leaf surface area ( A ) with linear leaf dimensions was best described by the Montgomery equation (ME) that describes A as the product of leaf length ( L ) and width ( W ). Following from ME, a proportional relationship between A and the square of L has been proposed, but the validity of this simplified equation strongly depends on leaf shape ( W/L ratio). Here, we show that the simplified equation can be applied to a group of closely related plants sharing a similar W/L ratio with low degree of uncertainty. We measured A , L and W of more than 10,000 leaves from 101 graminoid taxa (subfamily Bambusoideae) having similar elongated leaf shapes. We found that ME applies to the leaves of all bamboo taxa investigated. The power law equation that was used to describe a scaling relationship of A vs. L also predicted leaf area with high accuracy, but the variability measured as the root-mean-square error (RMSE) was greater than that using ME, indicating that leaf width also plays an important role in predicting leaf area. However, the dependence of the prediction accuracy of A on W is intimately associated with the extent of the variation in W/L ratio. There was a strong positive correlation ( r = 0.95 for the 101 bamboo taxa) between RMSE and the coefficient of variation in W/L ratio. Thereby, our results show that leaf area of bamboo plants can be calculated by the product of L and W with a proportionality coefficient ranging from 0.625 to 0.762, i.e., the leaf area of bamboo leaves approximately equals 70% of a rectangular area formed by L and W . The pooled data of ln( A ) vs. ln( WL ) of 101 bamboo taxa were located on or very close to the regression line without being affected by interspecific differences. However, interspecific differences in W/L ratio largely affected the scaling relationship of A vs. L , which led to large deviations of the data of ln( A ) vs. ln( L ) from the regression line. This implies that the square relationship between A and L does not apply to all species even if those are very closely related taxa.

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

A frameshift mutation in exon 19 of MLH1 in a Chinese Lynch syndrome family: a pedigree study - Qiao-qi Sui; Wu Jiang; Xiao-dan Wu; Yi-hong Ling; Zhi-zhong Pan; Pei-rong Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

Expression of a gene encoding a rice RING zinc-finger protein, OsRZFP34, enhances stomata opening - Kuo-Hsuan Hsu; Chia-Chin Liu; Shaw-Jye Wu; Ying-Yu Kuo; Chung-An Lu; Ching-Rong Wu; Pei-Jyun Lian; Chwan-Yang Hong; Yi-Ting Ke; Juin-Hua Huang; Ching-Hui Yeh (Plant Molecular Biology, 2014)

An overview of studies on psychological well-being in children born following assisted reproductive technologies - Qi-tao Zhan; Pei-pei Pan; Xiang-rong Xu; Hang-ying Lou; Yi-yun Lou; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2013)

Detection of expression of influenza virus receptors in tissues of BALB/c mice by histochemistry - Zhang-Yong Ning; Min-Yi Luo; Wen-Bao Qi; Bo Yu; Pei-Rong Jiao; Ming Liao (Veterinary Research Communications, 2009)

Effect of siRNA on HSV-1 plaque formation and relative expression levels of UL39 mRNA - Ren Zhe; Zhang Mei-Ying; Kaio Kitazato; Nobuyuki Kobayash; Zhu Qin-Chang; Zhang Pei-Zhuo; Yang Zhi-Rong; Wang Yi-Fei (Archives of Virology, 2008)

Induction of apoptosis in rabbit oral mucosa by 1.23% acidulated phosphate fluoride gel - Chia-Ling Tsai; Jui-Wei Lin; Hsi-Kung Kuo; Ming-Hong Tai; Yi-Chen Wu; Chih-Rong Shyr; Pei-Chang Wu (Archives of Toxicology, 2008)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)